Proposição de uma Estrutura Hierárquica de Indicadores de Inovação para Avaliação da Criação e Captura de Valor da Atividade Inovadora - Thamer, Rogério (2024)
Even with its recognized economic, academic and business relevance, how to measure and evaluate innovation continues to be a challenge for organizations. The absence of a dominant epistemological paradigm leads to a profusion of metrics, models and indicators that, in most cases, do not address innovation comprehensively. This research aims to propose a theoretical model for evaluating innovation, encompassing the perspectives that impact innovative activity in organizations. We also seek to present a structure for categorizing and hierarchizing innovation dimensions and indicators according to their level of priority and importance for innovation management, which allows us to identify whether the firm is prepared to innovate, create and capture value from this activity. This work achieves its objectives through the aggregation of opinions from experts in the field, collected using a combination of Delphi and AHP methods, resulting, as a contribution, in a new hierarchical structure of innovation dimensions, which are relevant for monitoring the creation and capture value throughout innovative activity. This contribution will, in a practical way, allow organization managers to evaluate, select and prioritize indicators, in such a way as to offer greater clarity in the construction of innovation assessment systems.